Visible and Near-IR Nano-Optical Components and Systems in CMOS - Kaushik Sengupta; Lingyu Hong; Chengjie Zhu; Xuyang Lu (IEEE Open Journal of the Solid-State Circuits Society, 2021)
Integration of complex optical systems operating in the visible and near-IR range (VIS/NIR), realized in a CMOS fabrication process in an absolutely ‘no change’ approach, can have a transformative impact in enabling a new class of miniaturized, low-cost, smart optical sensors and imagers for emerging applications. While ‘silicon photonics’ has demonstrated the path towards such advancements in the IR range, the field of VIS/NIR integrated optics has seen less progress. Therefore, while currently ultra high-density and higher performance image sensors are commonplace in CMOS, all passive optical components (such as lenses, filters, gratings, collimators) that typically constitute a high-performance sensing or imaging system, are non-integrated, bulky and expensive, severely limiting their application domains. Here, we present an approach to utilize the embedded copper-based metal interconnect layers in modern CMOS processes with sub-wavelength feature sizes to realize multi-functional nano-optical structures and components. Based on our prior works, we illustrate this electronic-photonic co-design approach exploiting metal/light interactions and integrated electronics in the 400nm-900 nm wavelengths with three design examples. Realized in 65-nm CMOS, these demonstrate for the first time: fully integrated multiplexed fluorescence based biosensors with integrated filters, optical spectrometer, and CMOS optical physically unclonable function (PUF). These examples cover a range of optical processing elements in silicon, from deep sub-wavelength nano-optics to diffractive structures. We will demonstrate that when co-designed with embedded photo-detection and signal processing circuitry, this approach can lead to a new class of millimeter-scale, intelligent optical sensors for a wide range of emerging applications in healthcare, diagnostics, smart sensing, food, air quality, environment monitoring and others.